Quantitative assessment of adipocyte differentiation in cell culture. (1st October 2016) - Kraus, Nils A.; Ehebauer, Franziska; Zapp, Benedikt; Rudolphi, Bianca; Kraus, Bettina J.; Kraus, Daniel
ABSTRACT: Adipocyte cell culture is an important tool for mechanistic studies of energy metabolism. Many factors affect the differentiation of adipocytes in culture. Oil red O staining can be used to assess the degree of differentiation. However, the validity of this method for quantitative analysis has not yet been established. Here we show that a protocol with arbitrarily chosen parameters does not measure in the linear range and is not suitable for quantitative analysis (R 2 = 0.077, p = 0.382), and develop and validate an optimized protocol for quantitative oil red O staining of cultured adipocytes. 3T3-L1 preadipocytes and adipocytes are fixed with 4% formaldehyde and stained with 0.2% oil red O solution in 40% 2-propanol for 30 minutes. Dye is eluted with 2-propanol, and absorption of the eluate is measured photometrically at 510 nm. This optimized protocol achieves excellent correlation between defined amounts of differentiated adipocytes on constant-size culture plates and photometric absorption (R 2 = 0.972, p = 6.585E-14). The performance of the method is independent of the culture plates used. Thus, the optimized oil red O staining protocol can be universally employed to quantitatively assess adipocyte differentiation.